Evaluation of a Tennessee statewide initiative to reduce early elective deliveries using quasi-experimental methods - Michael P. Thompson; Ilana Graetz; Caitlin N. McKillop; Peter H. Grubb; Teresa M. Waters (BMC, 2019)
Abstract Background Concerted quality improvement (QI) efforts have been taken to discourage the practice of early elective deliveries (EEDs), but few studies have robustly examined the impact of directed QI interventions in reducing EED practices. Using quasi-experimental methods, we sought to evaluate the impact of a statewide QI intervention to reduce the practice of EEDs. Methods Retrospective cohort study of vital records data (2007 to 2013) for all singleton births occurring ≥36 weeks in 66 Tennessee hospitals grouped into three QI cohorts. We used interrupted-time series to estimate the effect of the QI intervention on the likelihood of an EED birth statewide, and by hospital cohort. We compared the distribution of hospital EED percentages pre- and post-intervention. Lastly, we used multivariable logistic regression to estimate the effect of QI interventions on maternal and infant outcomes. Results Implementation of the QI intervention was associated with significant declines in likelihood of EEDs immediately following the intervention (odds ratio, OR = 0.72; p < 0.001), but these results varied by hospital cohort. Hospital risk-adjusted EED percentages ranged from 1.6-13.6% in the pre-intervention period, which significantly declined to 2.2-9.6% in the post-intervention period (p < 0.001). The QI intervention was also associated with significant reductions in operative vaginal delivery and perineal laceration, and immediate infant ventilation, but increased NICU admissions. Conclusions A statewide QI intervention to reduce EEDs was associated with modest but significant declines in EEDs beyond concurrent and national trends, and showed mixed results in related infant and maternal outcomes.